Cicerono Tryliktoji filipika: dialogas su nesančiu žmogumi - Kučinskienė, Audronė (Literatūra, 2009)
The publication consists of the first published translation of Cicero’s Thirteenth Philippic into Lithuanian, accompanied by an article which analyses the use of the letter by Mark Antony in this speech (Phil. XIII, 22–48). In the Thirteenth Philippic, whose main purpose is to characterise Mark Antony and his followers, one can detect more traits of an invective than in any other Philippic. This is what makes this speech stand out in the whole set of the Philippics, and makes it close to the Second Philippic, which is not a speech in the strict definition of the genre, but a political pamphlet and a specimen of a Roman invective. The conventions of a Roman invective, which allow for unrestrained denigration of the opponent, and strong exaggeration or even distortion of facts, create certain patterns, repetitive places (loci communes, topoi). In this way the usual sallies against one’s personal life, family, habits and vices become formulaic and ineffective. This is why Cicero chooses more subtle forms of derision, as if transgressing the boundaries of the traditional obloquy: in the Second Philippic he creates an impression of a comedy by making Mark Antony to appear as character of a comedy, and in the Thirteenth Philippic Cicero characterises him by quoting and commenting on his letter. The Thirteenth Philippic stands out in several aspects. Firstly, since a letter is being quoted, one can speak of a fusion of two distinct literary genres, both in their nature close to dialogue, and of maximum use of the possibilities offered by the dialogue genre. Also, the genre of a letter itself is of dialogic nature and, as well as an orator’s speech and a diatribe, can be considered a borderline phenomenon between a dialogue and a monologue. Secondly, the Thirteenth Philippic is probably the unique extant instance of dialogic quoting not only among Cicero’s speeches but also in the whole Roman rhetoric, when another author’s text, in this case, the letter of Mark Antony, is quoted in its entirety. If we excerpt the quotations of the letter from the text of the speech and join them together, we get a coherent, logical, and complete text of the letter. Starting with the salutation, Cicero successively reads the whole of the letter, inserting his ironic remarks between the passages. The speaker not just conveys the contents of the quoted document, but he disputes with the text of the quotation, as if engaged into a dialogue with it. An alien phrase, surrounded by such context, inevitably becomes involved into dialogic relations, and any shade of meaning can be imposed onto it according to the orator’s plan. Nevertheless, the quoting of the entire letter does not become monotonous, as the orator masterfully varies the form of the dialogue: sometimes he reads only one sentence from the letter and responds to it with one or several phrases (Phil. XIII, 22; 36; 40; 46 etc.); sometimes the response is long and exhaustive, in which case the quotation from the letter acts only as a pretext to speak out the ideas that the orator wishes to say (26–30). Especially vivid and realistic impression of a conversation is created in those cases where the quotation is divided into small segments, and, as if interrupting his interlocutor, the orator inserts his own remarks into the interlocutor’s text (24–25; 30–34). Thus the form of a dialogue and the stance of the orator as an ironic interlocutor allow Cicero to interpret the contents of the letter in his own way and to present the author of the letter in a certain unfavourable light.